Ways to reduce nitrate content in vegetables - Bazarbayev Ajiniyaz (Genius Publishing Group, 2024)
The article defines such concepts as nitrates and nitrites, reveals their role in the modern world. The problem of dependence of human health on the quality of agricultural products and nutrition is also considered. A brief description of nitrates, their origin and impact on plants and human health is given. The causes of nitrate accumulation in vegetables, as well as their distribution among plant parts are revealed. the norm of their content in the body is determined. At the end of the article, recommendations are given to reduce the content of nitrates in the human body
Keywords: nitraty; noisemaker; ecotoxicant